2013
DOI: 10.1155/2013/182132
|View full text |Cite
|
Sign up to set email alerts
|

3,5,4′-tri-O-acetylresveratrol Ameliorates Seawater Exposure-Induced Lung Injury by Upregulating Connexin 43 Expression in Lung

Abstract: The aim of the present study was to examine the effects of 3,5,4′-tri-O-acetylresveratrol on connexin 43 (Cx43) in acute lung injury (ALI) in rats induced by tracheal instillation of artificial seawater. Different doses (50, 150, and 450 mg/kg) of 3,5,4′-tri-O-acetylresveratrol were administered orally for 7 days before modeling. Four hours after seawater inhalation, histological changes, contents of TNF-α, IL-1β and IL-10, and the expression of Cx43 in lungs were detected. Besides, the gap junction communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…The hyperosmolar seawater has direct effect on the lung epithelial cells and causes the infiltration of inflammation cells into the alveolar spaces and releases various molecules, leading to lung edema and deterioration of gas exchange [3][4][5][6]15]. Proinflammatory cytokines, such as TNF-α and IL-6, are critical for initiating, amplifying, and perpetuating organ injury [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…The hyperosmolar seawater has direct effect on the lung epithelial cells and causes the infiltration of inflammation cells into the alveolar spaces and releases various molecules, leading to lung edema and deterioration of gas exchange [3][4][5][6]15]. Proinflammatory cytokines, such as TNF-α and IL-6, are critical for initiating, amplifying, and perpetuating organ injury [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…(ii) Resveratrol group (n 10). Same as the BLM + vehicle group, but resveratrol was administered by oral route (50 mg/kg) (28) , immediately after BLM instillation and daily for 7 d. (iii) Mangiferin group (n 10). Same as the BLM + vehicle group but Mangifera indica leaf extract, containing ≥60 % mangiferin, was administered by oral route (10 mg/kg) (27) , immediately after BLM instillation and daily for 7 d. (iv) Quercetin group (n 10).…”
Section: Experimental Groupsmentioning
confidence: 99%
“…Evidence has demonstrated that it exerted anti-γ-irradiation effects by inhibiting the expression of reactive oxygen species (ROS) (26). Additionally, in a previous study it was demonstrated that acetylated resveratrol attenuated SW-ALI by interfering with intracellular communication (27) and the HIF-1α pathway (28). The aim of the present study was to examine the values of the NF-κB and i-NOS pathways in SW-ALI and the effects of AC-Res in seawater-stimulated lungs.…”
Section: Discussionmentioning
confidence: 99%